Half century of protected area dynamism in the country of Gross National Happiness, Bhutan. Issue 7 (23rd April 2019) - Dorji, Tshering; Linke, Simon; Sheldon, Fran
Abstract: Bhutan is recognized for conservation success under its pro‐environmental development philosophy Gross National Happiness (GNH). However, an increase in area coverage alone cannot track the true contribution of protected areas (PAs) to biodiversity conservation. Capturing PA dynamism by tracking PADDD (PA downgrading, downsizing, and degazettement) and gain events can be used as a more comprehensive evaluation method. Based on existing data, we tracked gain events, enacted and proposed PADDD events, proximate causes of PADDD, and gain and PADDD events trends in Bhutan from 1966 to 2016. We also compared PADDD events recorded inwww.PADDDtracker.org with the primary data sourced for our study. We discussed the findings in light of four tenets of GNH: good governance, sustainable socioeconomic development, preservation, and promotion of culture, and environmental conservation. We identified 81 gain and 29 PADDD events. All 12 proposed policy downgrading events in 2004 were proximally caused by infrastructure development, while all degazettement ( n = 6) in 1993 and all downsizing events (two in 1984 and one in 1993) were proximally caused by conservation planning. Overall the gain and PADDD events were episodic but policy downgrading events occurred only from 2002. Based on our country data, we recorded 4.8 times more PADDD events than was recorded inwww.PADDDtracker.org where even some degazetted PAs were not recorded. All gain events and even PADDD events, excluding one enacted and 12 proposed policy downgrading events caused by hydropower projects were aimed to improve conservation thus aligning with tenets of GNH. However, as hydropower is the specific cause for all proposed PADDD, Bhutan should be concerned about PADDD. Our findings provide further evidence for the dynamic nature of PAs, the widespread nature of PADDD and difficulty in detecting it. Furthermore, they also suggest the need to conduct archival case studies to better detect PADDD and PA dynamism.